Assesment of Occupational Risks and Health Hazards among Healthcare Workers in A Ghanaian Hospital - Prah, James; Aggrey, Ebenezer; Andreas, Kudom; Abdulai, Mohammed; Banson, Cecil; Addo-Yeboa, Benedict; Arhin, Stephen (Universitas Negeri Semarang (UNNES) in cooperation with the Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
Information on measuring risks prevalent among healthcare workers in Ghana andglobally is limited. With anecdotal evidence suggesting a high level of occupational injuries among health workers working in a Ghanaian University Hospital, this studywas conducted to identify the common hazards faced by the health workers and use thedecision matrix risk assessment technique to determine the risks associated with somehazards identified. The study also determined these workers’ knowledge, attitude, awareness, and practices toward occupational health and safety. A triangulation of methods was used. The study used a survey, a review of incident registers, and an expertevaluation. There were a total of 133 participants made up of various health professional groups, with nurses and midwives being the majority (31.6%). Knowledge, attitude, awareness, and practices towards occupational health and safety were high.Knowledge scores were significantly associated with age groups (X2-18.996, p-0.001)and cadre of staff (X2-14.690, p-0.005). Attitude was significantly associated withage groups (X2-10.467, p-0.033), years of working (X2-11.112, p-0.011), and cadreof staff (X2-15.467, p-0.004). Awareness was significantly associated with years ofworking (X2-8.57, p-0.035). There was a high prevalence of self-reported needle stickinjuries. A review of incident registers revealed a high underreporting rate of occupational injuries. Staff were found to be at high risk of musculoskeletal injuries and stress.